Design of a Microgrid with Low-Voltage Ride-Through Capability and Simulation Experiment. (9th June 2014) - Fan, Wenchao; Wu, Zaijun; Dou, Xiaobo; Hu, Minqiang; Wei, Jieru; Lv, Zhenyu
Abstract : A microgrid with low-voltage ride-through capability is designed. The designed microgrid avoids operating in unplanned islanded mode during an asymmetric ground fault which occurs in the low voltage distribution network and supports fault recovery for distribution network. Furthermore, compared with the traditional microgrid topology, the proposed microgrid topology also saves a lot of power electronic devices. The simulation results with PSCAD/EMTDC show that the microgrid can keep the distributed generations and loads operate normally when an asymmetric ground fault occurs in the low voltage distribution grid. It can also increase the active power output according to the requirement of the distribution network to support the distribution network fault recovery.